2012
DOI: 10.1039/c2jm15747k
|View full text |Cite
|
Sign up to set email alerts
|

Direct formation of organic semiconducting single crystals by solvent vapor annealing on a polymer base film

Abstract: We report single crystal formation of organic semiconducting small molecules via solvent vapor annealing (SVA) on a polymer base film (PBF). The soluble PBF strongly assists the self-assembly of small molecules to form single crystals; this sharply contrasts typical SVA where the inorganic base film such as SiO 2 plays little or no role. We use a matrix of organic solvents and polymers to systematically investigate the re-crystallization of dioctylbenzothienobenzothiophene (C8-BTBT) by SVA on polymer surfaces.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
72
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 32 publications
2
72
0
Order By: Relevance
“…In this study, we thermally treated NTCDI-Cn thin films prepared by a solution process. Although annealing based on solvent vapor (solvent vapor annealing) is widely used, especially in solution-processed organic semiconductor thin films [29][30][31], we opted for simple thermal annealing in this study. …”
Section: Introductionmentioning
confidence: 99%
“…In this study, we thermally treated NTCDI-Cn thin films prepared by a solution process. Although annealing based on solvent vapor (solvent vapor annealing) is widely used, especially in solution-processed organic semiconductor thin films [29][30][31], we opted for simple thermal annealing in this study. …”
Section: Introductionmentioning
confidence: 99%
“…While attempting oriented growth of organic crystals, a process known as polymer-assisted solvent vapor annealing (PASVA) was studied and developed further for preparing organic crystals in special forms [235,454]. For instance, C8-BTBT was prepared as a rod-like structure with good air-stability and high mobility [235,454,455] using PASVA, an all-solution process for growing quality organic crystals at room temperature.…”
Section: Special Os Crystalsmentioning
confidence: 99%
“…For instance, C8-BTBT was prepared as a rod-like structure with good air-stability and high mobility [235,454,455] using PASVA, an all-solution process for growing quality organic crystals at room temperature. The PASVA process helps in reorganizing the molecules into several hundred micron-sized single crystals in length.…”
Section: Special Os Crystalsmentioning
confidence: 99%
“…Although some reports have focused on the effects of solvent vapor on films of organic semiconductors, [18][19][20][21][22][23][24][25] growth of single crystal films with transitions of crystal structure has not been reported. This study shows that polymorphic materials are applicable for single crystal film fabrication by a simple solution process.…”
mentioning
confidence: 99%
“…13 Therefore, to obtain solution-processed films with highly ordered crystal structure, novel printing processes have been reported that focus on the behavior of molecules in drying solutions. [14][15][16][17] In addition, simple treatments under solvent vapor after film fabrication are also effective for improving the crystallinity [18][19][20][21] and the size of the domains in the films. [21][22][23][24][25] Although effects of solvent vapor on transitions of crystal structures are also prospective, detailed studies of the transitions of crystal structures have not been conducted.…”
mentioning
confidence: 99%